Alterations in the blood brain barrier in ageing cerebral cortex in relationship to Alzheimer-type pathology: a study in the MRC-CFAS population neuropathology cohort - SAVVA, GEORGE (Elsevier, 2011)
Impairment of the blood brain barrier (BBB) in human brain ageing and its relationship to Alzheimer-type pathology remains poorly defined. We have investigated the BBB in temporal cortex of brain donations from a population-representative sample of 92 participants from the Medical Research Council Cognitive Function and Ageing Study (MRC CFAS), a longitudinal study with a programme of brain donation. BBB alteration was investigated by immunohistochemistry to albumin and fibrinogen and to the tight junction proteins claudin-5, zonula occludens-1 (ZO-1) and occludin. BBB leakage showed wide population-variation and increased with progression of Alzheimer-type pathology, though with considerable overlap between different levels of Alzheimer-type pathology. This was accompanied by increased mean vascular density, but not by down-regulation of tight junction proteins. ZO-1 and occludin were also expressed in glia. Mechanisms leading to BBB leakage in brain ageing remain to be defined, but the population-variation in BBB changes and its early increase in relationship to Alzheimer-type pathology progression suggest that BBB dysfunction contributes to brain ageing.
PUBLISHED
Keywords: Neuroscience; Alzheimer's disease; blood brain barrier; tight junction proteins; brain ageing